Disposable on‐chip microfluidic system for buccal cell lysis, DNA purification, and polymerase chain reaction. Issue 17 (2nd August 2013) - Cho, Woong; Maeng, Joon‐Ho; Ahn, Yoomin; Hwang, Seung Yong
<x xml:space="preserve">Abstract</x> This paper reports the development of a disposable, integrated biochip for DNA sample preparation and PCR. The hybrid biochip (25 × 45 mm) is composed of a disposable PDMS layer with a microchannel chamber and reusable glass substrate integrated with a microheater and thermal microsensor. Lysis, purification, and PCR can be performed sequentially on this microfluidic device. Cell lysis is achieved by heat and purification is performed by mechanical filtration. Passive check valves are integrated to enable sample preparation and PCR in a fixed sequence. Reactor temperature is needed to lysis and PCR reaction is controlled within ±1°C by PID controller of LabVIEW software. Buccal epithelial cell lysis, DNA purification, and SY158 gene PCR amplification were successfully performed on this novel chip. Our experiments confirm that the entire process, except the off‐chip gel electrophoresis, requires only approximately 1 h for completion. This disposable microfluidic chip for sample preparation and PCR can be easily united with other technologies to realize a fully integrated DNA chip.